2022
DOI: 10.3389/fnmol.2021.792364
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3 Inhibitors: Preclinical and Clinical Focus on CNS-A Decade Onward

Abstract: The protein kinase, GSK-3, participates in diverse biological processes and is now recognized a promising drug discovery target in treating multiple pathological conditions. Over the last decade, a range of newly developed GSK-3 inhibitors of diverse chemotypes and inhibition modes has been developed. Even more conspicuous is the dramatic increase in the indications that were tested from mood and behavior disorders, autism and cognitive disabilities, to neurodegeneration, brain injury and pain. Indeed, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 376 publications
(467 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, in our study, we propose the use of reprogramming with BIO for adoptive cell therapies. Given the multisystemic effects that GSK3-targeting drugs could have in vivo ( 78 ), it will be necessary to explore the use of other GSK3 inhibitors with proven clinical safety and tolerability ( 78 , 79 ) that could be injected systemically to reprogram CD8 + T cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, we propose the use of reprogramming with BIO for adoptive cell therapies. Given the multisystemic effects that GSK3-targeting drugs could have in vivo ( 78 ), it will be necessary to explore the use of other GSK3 inhibitors with proven clinical safety and tolerability ( 78 , 79 ) that could be injected systemically to reprogram CD8 + T cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that the main phytochemicals that target these molecules are butyl-β- D -fructopyranoside (13 targets), oxyhylladiketone (13 targets), oxyphyllol B (12 targets), yakuchinone B (12 targets), 5-HYD (11 targets), tectochrysin and β- D -glucopyranoside (11 targets), and 1-methyl butyl (11 targets) ( Figure 8B ). GSK3β (encoded by GSK3B) has been demonstrated to be important in neuronal death ( Arciniegas and Eldar-Finkelman, 2021 ). Molecular docking results showed that 5-HYD, rhamnetin, β- D -glucopyranoside, 2-hydroxy-5-methoxyphenyl, rhamnocitrin, and (S)-1-phenylethyl β- D -glucopyranoside had strong binding affinities for GSK3β ( Figure 8C ).…”
Section: Resultsmentioning
confidence: 99%
“…GSK-3β plays a key role in axon regeneration. Inactivation of GSK-3β promotes axonal growth and neurological recovery in the central nervous system ( Arciniegas Ruiz and Eldar-Finkelman, 2021 ; Rodriguez-Jimenez et al, 2021 ). MiR-22-3p derived from adipose-tissue MSC exosomes can alleviate cerebral ischemia injury by inhibiting the BMP2/BMF axis mediated by kdm6b.…”
Section: Exosomes and Mesenchymal Stem Cellsmentioning
confidence: 99%